Cytomegalovirus pneumonia presenting as pulmonary nodules - Basinger, Janet; Kapp, Meghan E. (Autopsy and Case Reports, 2022)
Cytomegalovirus (CMV) pneumonia is a well-known cause of morbidity and mortality in patients with a history of allogenic hematopoietic stem cell transplant. Radiographically, CMV pneumonia most commonly presents as bilateral ground glass opacities; however, the presentation is non-specific and can be variable, including presenting as areas of air-space consolidation or pulmonary nodules. We report a case of a 70-year-old man who presented with rapidly progressive bilateral pulmonary nodules approximately two months after receiving a bone marrow transplant. No infectious etiology was identified for the pulmonary nodules, and a bronchoscopy was unable to be performed due to a rapid decline in the patient’s overall condition and respiratory status. The patient died shortly after the decision was made to transition to palliative care and a limited autopsy was performed to explore the pulmonary findings. Corresponding to premortem imaging were the postmortem gross findings of numerous bilateral pulmonary nodules and a large mass-like area of consolidation in the right upper lobe. Microscopic examination of the nodules demonstrated a necrotizing pneumonia with few foci of viral cytopathologic change consistent with CMV, which was confirmed by immunohistochemistry. While CMV is a common infectious agent in the immunocompromised population, CMV pneumonia continues to be a challenging entity due to difficulty in diagnosis and treatment. Rapidly enlarging pulmonary nodules in an immunosuppressed patient is highly suggestive of an infectious process and careful histologic examination for viral cytopathologic change is essential.